Knights in shining armour and (M)others in life jackets: Women’s experiences of advocating for care alone when suffering recurrent early pregnancy loss during the SARS-CoV-2 pandemic - Flora E. Kent-Nye; Kayleigh S. Sheen; Karen Burgess; Munira Oza; Laura A. Magee; Davor Jurković; Sergio A. Silverio (BMC Public Health)
Abstract Background Recurrent early pregnancy loss [rEPL] is a traumatic experience, marked by feelings such as grief and depression, and often anxiety. Despite this, the psychological consequences of rEPL are often overlooked, particularly when considering future reproductive health or approaching subsequent pregnancies. The SARS-CoV-2 pandemic led to significant reconfiguration of maternity care and a negative impact on the perinatal experience, but the specific impact on women’s experience of rEPL has yet to be explored. This study aimed to examine the impact of changes to early pregnancy loss care and social restrictions during the pandemic on women’s experience of rEPL. Methods A qualitative interview study design was employed, with semi-structured interviews conducted virtually. A total of 16 women who had suffered two or more early pregnancy losses (≤ 14 weeks gestation) during the SARS-CoV-2 pandemic in the United Kingdom participated. Data were recorded, transcribed, and analysed by hand, following a Classical Grounded Theory Analysis, appropriate for cross-disciplinary health research. Results Iterative and inductive analysis generated the theory ‘Knights in Shining Armour and (M)others in Life Jackets’, which describes women’s experience of advocating for care alone, when suffering rEPL during the pandemic. This theory was derived from the way in which three emergent themes inter-related: (1) Dismantling Validation; (2) Preserving an Identity of Motherhood; and (3) Support Waning. Conclusions This study affirms recent findings of devalued maternity care during the pandemic, and magnification of pre-pandemic issues with EPL care, such as a lack of support or perceived empathy.